Effective Synchronization of a Class of Chua’s Chaotic Systems Using an Exponential Feedback Coupling - Patrick Louodop; Hilaire Fotsin; Elie B. Megam Ngouonkadi; Samuel Bowong; Hilda A. Cerdeira (Abstract and Applied Analysis)
A robust exponential function based controller is designed to synchronize effectively a given class of Chua's chaotic systems. The stability of the drive-response systems framework is proved through the Lyapunov stability theory. Computer simulations are given to illustrate and verify the method.